EFEKTIVITAS PROGRAM PUSKESMAS TANPA ANTRIAN KOTA SEMARANG (PUSTAKA) PADA PENDAFTARAN ONLINE DI PUSKESMAS SRONDOL BANYUMANIK SEMARANG - Enggareti, Viskarani Bertys; Widowati, Nina; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2022)
As a form of effort to fulfill health services for the community by utilizing technological developments, the Semarang City Health Service issued the Semarang City No Queue Health Center (PUSTAKA) program for all health centers in Semarang City which is a form of public service innovation in the form of online registration to reduce queues for registration of treatment throughout the city. health center in the city of Semarang. Srondol Health Center is one of the health centers in Semarang City which has started using the PUSTAKA program for online registration for patients who register. The problem encountered is that the number of users of the PUSTAKA program is still small, so the queue for registration for treatment is still long. This study aims to analyze the effectiveness of the PUSTAKA program at the Srondol Health Center and also to see the obstacles faced in running the PUSTAKA program. This study uses descriptive qualitative methods, and uses the theory of public administration, public services, and program effectiveness. The research respondents came from the PUSTAKA Admin of the Srondol Health Center, the Semarang City Health Office and the public using the PUSTAKA program. The results showed that the PUSTAKA program had not run effectively at the Srondol Health Center due to several obstacles including: (1) lack of human resources, (2) no clear procedures, (3) lack of staff skills, (4) inadequate infrastructure, and (5) lack of socialization by officers. Recommendations from researchers to increase the effectiveness of the PUSTAKA program are by increasing the number of human resources, making clear procedures about PUSTAKA, improving the facilities used, and more often socializing to the public about the PUSTAKA program